Obsessive compulsive disorder in an adult patient with Gilles de la Tourette syndrome and expressed behavioral disorders (clinical case). - L. Yuryeva; T. Shusterman; Ya. Varshavskyi; V. Malyshko (Medičnì Perspektivi)
The article describes the clinical case of obsessive-compulsive disorder in an adult patient with Gilles de la Tourette syndrome and severe behavioral disorders. The authors demonstrated the comorbidity of Gilles de la Tourette syndrome and obsessive-compulsive disorder. Obsessive thoughts and compulsive actions were diagnosed as the most frequent behavioral disorders in Tourette syndrome. It was indicated on gender as an additional sanctioning factor for the early onset of mental disorders. Obsessive-compulsive disorder in the patient was characterized by mixed obsessive thoughts and actions, had a protracted nature, with prolonged decompensations requiring treatment in a psychiatric hospital. Emotional instability, impulsivity, obsessions and compulsions affecting the social functioning of not only the patient himself, but also those around him, as well as pronounced behavioral disturbances led to social malajustment. When treating the patient, the doctors had to resort to a combination of typical neuroleptics with second-generation antipsychotics, mood stabilizers and antidepressants due to the poor response to pharmacotherapy. Comorbidity of mental disorders determined the complexity of therapeutic measures with the use of psychotherapeutic interventions, which made it possible to achieve an improvement in the mental state and avoid disability of the patient.